Cover Picture: Shape‐selective Valorization of Biomass‐derived Glycolaldehyde using Tin‐containing Zeolites (ChemSusChem 21/2016). Issue 21 (7th November 2016) - Tolborg, Søren; Meier, Sebastian; Saravanamurugan, Shunmugavel; Fristrup, Peter; Taarning, Esben; Sádaba, Irantzu
Abstract : The Cover picture shows that if a suitable zeolite framework is chosen biomass can be converted to tetrose sugars due to shape selctivity. These sugars are not easily obtained from other sources and have potentially high value. However, hexose sugars are also obtained in this reaction and it is, therefore, important to identify catalysts that have a high selectivity towards C4 molecules. Zeolites with a defined pore structure are good candidates as they are known to offer good shape‐selectivity. With this in mind, we used a medium‐pore‐size zeolite modified with Sn (Sn‐MFI) to catalyze a very selective condensation of glycolaldehyde to tetroses, avoiding almost completely the further formation of higher sugars. More details can be found in the Full Paper by Tolborg et al. onpage 3054 in Issue 21, 2016 (DOI:10.1002/cssc.201600757 ).